Ordinary things and their extraordinary meanings - Marsico, Giuseppina; Tateo, Luca (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
The book provides a new look at the everyday relationship between psychological processes and extraordinary aspects of ordinary phenomena. Why should we deal with ordinary things? People's life is made of everyday practical, taken-for-granted things, such as driving a car, using money, listening music, etc. When you drive from home to workplace, you are migrating between contexts. Is this an empty space you are crossing, or the time you spend into the car is something meaningful?In psychological terms, things have, at least, three levels of existence, a material, a symbolic and an affective one. The underlying idea is that the symbolic elaboration of everyday things is characterized by the transcendence of the particular object-sign, leading to the creation of more and more complex sign fields. These fields expand according to an inclusive logic up to dialogically and dialectically incorporate opposites (i.e. clean/dirty, transparent/opaque, hide/ show, join/divide, slow/fast, etc.). Even the meaning of "ordinary" and "extraordinary" follow such an inclusive logic: if you give a positive value to ordinary, extraordinary is rule-breaking; otherwise, if ordinary means trivial, extraordinary assumes a positive value. Besides, things are cultural artifacts mediating the experience of the world, the psychological processes and the construction of mind. Reflecting upon "things" is thus a more meaningful pathway to understand Psyche.
Keywords: Material culture -- Psychological aspects.; Material culture -- Social aspects.; Relevance.; Meaning (Psychology); Social Science -- Anthropology -- Cultural & Social.; Social and cultural anthropology.; elektronické knihy; electronic books